Accession of the European Union to the European Convention on Human Rights from the perspective of the Common Foreign and Security Policy - Masło, Krzysztof (European Integration Studies, 2024)
According to Article 6 of the Treaty on the Functioning of the European Union, the European Union (EU) is obliged to access the European Convention on Human Rights (ECHR). Accession to the ECHR is particularly important in the context of Common Foreign and Security Policy (CFSP). The work carried out on the basis of which the EU will accede to the ECHR should aim to shape the future accession agreement so that it not only resolves the problem of judicial control over the CFSP and the compatibility of the law created with the standards developed by the European Court of Human Rights (ECtHR) but also, above all, addresses the relationship between the CJEU and the ECtHR in the context of the deficit of judicial control of the Court of Justice of the European Union (CJEU) over the law created under the CFSP and the practice of the functioning of this policy. This article thus focuses on previous works concerning EU accession to the ECHR, possible solutions to problematic questions, and the importance of the ECHR to the CFSP. The process of accession to the ECHR has shown that the introduction of an explicit legal basis in the treaties authorising the EU to do so has proven insufficient and created new problems which have in turn proved difficult to solve in practice.